Obese Children with Metabolic Syndrome Have 3 Times Higher Risk to Have Nonalcoholic Fatty Liver Disease Compared with Those without Metabolic Syndrome. (8th October 2017) - Papandreou, Dimitrios; Karavetian, Mirey; Karabouta, Zacharoula; Andreou, Eleni
Abstract : Background . The aim of this study was to investigate the relationship between metabolic syndrome (MS) and nonalcoholic fatty liver disease (NAFLD) in obese children. One hundred and twenty-five subjects aged 11-12 years old participated in the study. Methods . Anthropometric and biochemical indices were measured, including lipid and liver profile, blood glucose, serum insulin, and liver ultrasound. Results . Forty-four children (58.6%) were found to have MS. Insulin resistance was present in 78 (62.4%) children. Patients with MS were more likely to have NAFLD (P < 0.001 ). Children with NAFLD had significantly higher body mass index, waist circumference, triglycerides, fasting insulin, and lower high-density lipoprotein compared to patients with normal livers (P < 0.001 ). Insulin resistance was significantly higher in children with NAFLD (P < 0.001 ). Obese children presenting with MS were 3.01 (2.87–3.57, P < 0.002 ) times more likely to develop NAFLD compared to those without metabolic syndrome after adjustment of cofounders. Conclusions . Obese children with MS have a higher risk of developing NAFLD. Weight management and early prevention should be the first line of treatment to prevent any possible health issues later on.